PTH-074 Small bowel capsule endoscopy in the investigation of iron deficiency anaemia: referral patterns and clinical outcomes. (23rd September 2015) - Koulaouzidis, A; Douglas, S; Naismith, H; Plevris, J
Abstract : Introduction: Small Bowel capsule endoscopy (SBCE) is a useful diagnostic modality in the investigation of patients with Obscure Gastrointestinal bleed (OGIB)/Iron deficiency anaemia (IDA) when prior bi-directional endoscopies are negative. Methods: We retrospectively analysed data from patients referred to our tertiary centre for investigation of unexplained IDA, after negative bidirectional endoscopies. We aimed to establish referral patterns and clinical outcomes following SBCE. Results: Over a 5-year period (2004–2009), 133 patients (51 males, 82 females/mean age: 59.7) with unexplained IDA were referred to our service. Of those, 18 were referred from District General Hospitals (DGH) of South East Scotland, 106 from the Medical/Surgical Gastrointestinal (GI) service of our centre, 8 from the regional Haemophilia/Coagulation Medicine Centre (HCMC) and 1 from Renal medicine. One hundred and thirteen (n: 113/84.9%) patients were ≥40 years of age; in this group, small bowel angioectasias was the prevailing diagnosis (33/113, 29.2%), followed by Crohn's (9/113, 7.9%), while portal hypertension GAVE/PHG (9/113, 7.9%) and undiagnosed caecal angiodysplasias (5/113, 4.42%) formed an appreciable group (12.3%). One case of coeliac and one of lymphoma were also diagnosed, together with three cases of NSAID's-related enteropathy. SBCE was normal in 58 cases (51.3%). In the group of those <40 (n: 17), 10 had normal SBCE (58.2%), 2 had Crohn's (11.7%), 2 small bowel angioectasias (11.7%), while 1 case of Meckel's diverticulum and 1 case of capsule retention was seen. No small bowel malignancies were diagnosed in this group. Interestingly, the percentage of normal investigations was around 50%, irrespective of the source of referral (DGH 50%, HCMC 50%, and GI 51%). Small bowel angioectasias was the prevailing pathology irrespective of referral source (DGH 22%, HCMC 25%, GI 30.2%). Conclusion: In our cohort (patients with prior negative bidirectional tests), small bowel angioectasias are the prevailing cause of unexplained IDA irrespective of referral source. The referral source does not seem to impact on the percentage of normal SBCE. A significant proportion of those ≥40 years (12.3%), had pathologies missed by endoscopies. We recommend repeating bi-directional endoscopies in this age group, while on the waiting list for SBCE.